Darwinian evolution of entrepreneurial spirit and the process of development - Oded Galor; Stelios Michalopoulos (Brown University, Department of Economics, 2006)
This research suggests that a Darwinian evolution of entrepreneurial spirit played a significant role in the process of economic development and the evolution of inequality within and across societies. The study argues that entrepreneurial spirit evolved nonmonotonically in the course of human history. In early stages of development, the rise in income generated an evolutionary advantage to entrepreneurial, growth promoting traits and their increased representation accelerated the pace of technological advancements and the process of economic development. Natural selection therefore had magnified growth promoting activities in relatively wealthier economies as well as within the upper segments of societies, enlarging the income gap within as well as across societies. In mature stages of development, however, non-entrepreneurial individuals gained an evolutionary advantage, diminishing the growth potential of advanced economies and contribution to the convergence of the intermediate level economies to the advanced ones.
Keywords: O11; O14; O33; O40; J11; J13; 330; Entrepreneurial Spirit; Risk Aversion; Growth; Technological Progress; Evolution; Natural Selection; Entrepreneurship-Ansatz; Technischer Fortschritt; Evolutionsökonomik; Risikoaversion; Theorie